The face behind the law: The United Nations and the rights of indigenous peoples - Jackson, Moana (Yearbook of New Zealand jurisprudence, 2005)
In recent years Maori people have adopted many strategies to protect and advance the well being and visions implicit in the exercise of tino rangatiratanga. Much of that work has been done at home, but an increasing number of Iwi and other Maori organisations are now participating in international affairs that are seen to have some relevance to our lives. They are joining a worldwide movement by Indigenous Peoples to reassert their rights and reclaim their rightful place.
Keywords: UNDRIP; civil Rights; colonisation; crown law; imperialism; international law; international organization; racism; tiriti o waitangi/treaty of waitangi; waitangi tribunal